Analisis Pengaruh Service Quality, Food Quality, Value/Price Terhadap Customer Satisfaction - Rayyan Muhammad; Imron Rosyadi NR; Rina Susanti (Program Studi Teknik Industri Universitas Setia Budi, 2025)
Developments in the food and beverage sector are increasingly rapid; coffee shop businesses will experience an increase of 60.5% in 2022. Business actors will always strive for the best service for their customers. So, stakeholders must know the relationship between the services provided so that customers are satisfied. The purpose of this study was to see the magnitude of the relationship between service quality, presentation quality, value/price to customer satisfaction at Djamoean Café Pamekasan. The method used this time is structural equation modeling (SEM) with SmartPLS. This research shows that service quality has an AVE value <0.70, meaning that the service quality variable is not included in further analysis, the VIF value for all latent variables is below the threshold of 5, so there is no multicollinearity problem in the structural model. The first hypothesis looks for a positive influence of service quality on consumer satisfaction. This test shows that service quality has a positive effect on consumer satisfaction with a P value <0.05. The service quality reliability test showed that the results were unreliable, so service quality had no significant effect, so the first hypothesis was rejected. Serving quality has a positive influence on consumer satisfaction. The test results show that serving quality has a positive influence on consumer satisfaction with a P-value <0.05. So that hypothesis number two can be accepted. Value/price shows P-value> 0.05, then value/price does not have a positive effect on customer satisfaction. So that hypothesis number three is rejected. The author advises Djamoean Cafe Pamekasan to always maintain the quality of taste and hygiene of food and drinks, and provide sufficient serving portions to always provide customer satisfaction.